Current Understanding of Hearing Loss in Sporadic Vestibular Schwannomas: A Systematic Review - Gan, Jinlu; Zhang, Yanling; Wu, Jingnan; Lei, Deqiang; Zhang, Fangcheng; Zhao, Hongyang; Wang, Lei (Frontiers in Oncology, 2021)
Objective: Hearing loss is the most common initial symptom in patients with sporadic vestibular schwannomas (SVS). Hearing preservation is an important goal of both conservative and surgical therapy. However, the mechanism of SVS-associated hearing loss remains unclear. Thus, we performed this systematic review to summarize the current understanding of hearing loss in the SVS and distill a testable hypothesis to further illuminate its underlying mechanism. Methods: A systematic review querying four databases (PubMed, Medline, Embase, and Web of Science) was performed to identify studies evaluating hearing loss in patients with SVS and exploring the potential mechanisms of hearing impairment. Results: A total of 50 articles were eligible and included in this review. After analysis, the retrieved studies could be categorized into four types: (1) 29 studies explore the relationship between hearing loss and the growth pattern of the tumor (e.g., tumor size/volume, growth rate, tumor location, etc.); (2) ten studies investigate the potential role of cochlear dysfunction in hearing deterioration, including structural abnormality, protein elevation in perilymph, and cochlear malfunctioning; (3) two studies looked into SVS-induced impairment of auditory pathway and cortex; (4) in the rest nine studies, researchers explored the molecular mechanism underlying hearing loss in SVS, which involves molecular and genetic alterations, inflammatory response, growth factors, and other tumor-associated secretions. Conclusions: Multiple factors may contribute to the hearing impairment in SVS, including the growth pattern of tumor, cochlear dysfunction, impairment of auditory pathway and cortex, genetic and molecular changes. However, our current understanding is still limited, and future studies are needed to explore this multifactorial hypothesis and dig deeper into its underlying mechanism.